Analisis Penggunaan Database Dalam Meningkatkan Kualitas Sistem Informasi - Tiara Nurul Syahida; Nurul Hadianti; Yusromuin Munthe; Shara Jumiati Siregar; Nurbaiti Sirait (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study is to understand and analyze how to improve the quality of the system and the quality of information included in the informasibase. The methodology used in this study is a qualitative research method that builds on previous papers published by researchers and focuses on evaluating the literature with respect to specific components affecting the information management system. Each study shows that the quality of the system, the quality of information, and the quality of service are all in line with the expectations of system users. As system quality, information quality, and service quality all improve, user experience also improves. Informasibase is a very important component of an information management system, which also serves as a component of infrastructure, summation of information, assurance of information efficiency, and assurance of information effectiveness.